2003
DOI: 10.3201/eid0906.030009
|View full text |Cite
|
Sign up to set email alerts
|

Children with Respiratory Disease Associated with Metapneumovirus in Hong Kong

Abstract: Human metapneumovirus (HMPV) is a newly discovered pathogen thought to be associated with respiratory disease. We report the results of a study of 587 children hospitalized with respiratory infection over a 13-month period. HMPV was detected in the nasopharyngeal aspirates from 32 (5.5%) children by reverse transcription-polymerase chain reaction. HMPV infection was associated with clinical diagnoses of pneumonia (36%), asthma exacerbation (23%), or acute bronchiolitis (10%). When compared to those with respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
321
15
23

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 369 publications
(408 citation statements)
references
References 20 publications
49
321
15
23
Order By: Relevance
“…3/1000 inhabitants for infants aged <12 months and children aged 12-23 months, respectively) [25] but was lower than that observed in studies performed in Hong Kong (4 . 4/ 1000 inhabitants aged <6 years) [6] and South Africa (5 . 7/1000 human immunodeficiency virus uninfected children) [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3/1000 inhabitants for infants aged <12 months and children aged 12-23 months, respectively) [25] but was lower than that observed in studies performed in Hong Kong (4 . 4/ 1000 inhabitants aged <6 years) [6] and South Africa (5 . 7/1000 human immunodeficiency virus uninfected children) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that HMPV has a worldwide distribution and seasonal circulation, that it is a common respiratory pathogen in childhood, and that it contributes substantially to the aetiology and pathogenesis of lower respiratory tract infection (LRTI) [2][3][4][5][6][7]. Numerous studies have focused on the clinical and epidemiological characteristics of HMPV infection, but few have been population based, and consequently the available information on the incidence and burden of this disease remains scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Swab samples were subsequently tested using quantitative reverse-transcription PCR to detect influenza A virus and quantify virus shedding. Total nucleic acid was extracted using the NucliSens easy MAG extraction system (bioMerieux; Boxtel), according to the manufacturer's instructions, and 12 μL of extracted nucleic acid with a random primer was used to prepare complementary DNA with an Invitrogen Superscript III kit (Invitrogen), as described elsewhere [16]. Influenza A virus was detected with a PCR assay, as described elsewhere [17].…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…breathing difficulties, peaked at day five, whereas airway obstruction and hyperresponsiveness lasted until day 70. These latter observations along with earlier observation that HMPV may be associated to a subsequent history of asthma [13,24] in children make the mouse model an excellent tool for the study of the earlier steps of asthma history.…”
Section: Mouse Model (Balb/c)mentioning
confidence: 74%